Penyuluhan Sambungan Kayu dan Perbaikan Tangga Kayu Ruang Pertemuan Warga Kelurahan Bener, Kemantren Tegalrejo, Yogyakarta - Ade Lisantono; Egatama, Henda Febrian (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Bener Village is located in Tegalrejo District, Yogyakarta City, Special Region of Yogyakarta. The condition of infrastructure in Bener Village, especially in RT 10 RW 3, it was found that there were several buildings of wooden construction. One of the buildings with wooden construction is a resident's house which is also used for village resident’s meetings. Documentation from residents shows the condition of the building with damage to the stairs and wooden floor decks. Damage occurs due to poor wood quality and due to service life, as well as direct weather exposure. This Community Service aims to carry out repairs (renovations) on damaged infrastructure and increase public awareness about the importance of ensuring the quality of wood construction for the community, especially construction workers regarding wood connections. This service consists of three (3) stages, namely problem assessment, preparation of service, and implementation of service. This service has become a trigger in increasing public awareness about the importance of the correct application of wood construction as a building material. It has been attempted by holding counseling on construction and wood connection. In addition, the need to renovate the wooden stairs of the community meeting building has been fulfilled through this service by carrying out renovations in mutual cooperation between the service team and residents, using wood materials with a higher quality class and in accordance with the conditions at hand, namely direct weather exposure.